HPLC method for the simultaneous determination of four compounds in rat plasma after intravenous administration of Portulaca oleracea L. extract - Zhongzhe Cheng; Ming Xie; Wenjie Zhang; Lan Cheng; Yang Du; Yunjiao Wang; Xixiang Ying; Tingguo Kang (Universidade de São Paulo, 2012)
The objective of the present study was to develop a simple and selective HPLC method for the simultaneous determination of hesperidin (HP), caffeic acid (CA), ferulic acid (FA) and p-coumaric acid (p-CA) in rat plasma after intravenous administration of Portulaca oleracea L. extract (POE). With the hyperoside as the internal standard, the sample pretreatment procedure involved simple single-step extraction with methanol of 0.2 mL plasma. The mobile phase consisted of methanol-acetonitrile-tetrahydrofuran-0.5% glacial acetic acid (5:3:18:74, v/v/v/v). The calibration curves were linear over the range of 0.1-25 µg mL-1, 0.1-25 µg mL-1, 0.1-25 µg mL-1and 0.015-3 µg mL-1 for HP, CA, FA and p-CA, respectively. The method developed was suitable for the pharmacokinetic study of HP, CA, FA and p-CA in rats after intravenous administration of POE. O objetivo do estudo foi desenvolver um método simples e específico de HPLC para a determinação simultânea de hesperidina (HP), ácido caféico (CA), ácido ferúlico (FA) e ácido p-cumárico (p-CA) em plasma de rato após a administração intravenosa de extrato Portulaca oleracea L. (POE) empregando hyperosídeo como padrão interno de referência. Metanol foi empregado para os analitos em plasma (0,2 mL). A fase móvel isocrática foi composta por metanol-acetonitrila-tetraidrofurano-0,5% ácido acético glacial (5:3:18:74, v/v/v/v). Curvas de calibração foram lineares na faixa de concentração de 0,1-25 µg mL-1, 0,1-25 µg mL-1, 0,1-25 µg mL-1 e 0,015-3 µg mL-1 para HP, CA, FA e p-CA, respectivamente. O método desenvolvido foi adequado para estudo farmacocinético de HP, CA, FA e p-CA em ratos após a administração intravenosa de POE.